Documenting Illustrations; To Justify or Not to Justify ; Public Communication Campaigns; The Public Understanding of Science; Communicate! - Carol Sanders Reiner; Joyce Patterson; James W. King (Journal of Applied Communications, 1990)
Rreview of "Documenting nIustrations," by Mary C. Hester, Jacquelyn L. Monday. and John I. Snead ; "To Justify or Not to Justify," by Allan Haley; Public Communication Campaigns (Second Edition), edited by Ronald E. Rice and Charles K. Atkin; "The Public Understanding of Science," by J.R. Durnat, G.A. Evans, and G.P. Thomas; Communicate!, by the Philippine Association of Communication Educators.